Optimization of the lead removal from aqueous solution using two starch based adsorbents: Design of experiments using response surface methodology (RSM). Issue 1 (February 2019) - Bahrami, Mehdi; Amiri, Mohammad Javad; Bagheri, Fateme
Abstract: Starch phosphate as a novel adsorbent was synthesized for the removal of lead from aqueous media and characterized by BET, BJH, SEM, EDX, XRD, and FTIR techniques. SEM measurements demonstrated that the particle size of the synthesized starch was about 10 μm. XRD analysis showed that there is no significant difference between the potato starch and synthesized starch phosphate. It can be concluded that phosphorylation has not changed the crystalline structure of starch inside the granules. FTIR results verified the structure of two starch based adsorbents and EDX analysis confirmed the addition of phosphorus in the adsorbent structure. The adsorption batch experiments were conducted as a function of five effective parameters including pH (2–9), contact time (5–15 min), initial concentration of lead (30–250 mgL −1 ), temperature (20–60 °C), and adsorbent mass (0.03–0.25 g) using a central composite design (CCD) in response surface methodology (RSM). Contour and surface plots were used to determine the interaction effects of main factors and optimum conditions of process. The optimum level of the pH, temperature, initial concentration of lead, adsorbent dosage and contact time for maximum Pb 2+ removal (99.99%) were found to be 5.5, 37.5 °C, 63.57 mg L −1, 0.25 g, and 10 min, respectively. Results indicated that synthesized starch phosphate could be employed as an effective and versatile adsorbent for effluent decontamination particularly in Pb 2+ bearing wastewaters.